2012
DOI: 10.1089/met.2011.0075
|View full text |Cite
|
Sign up to set email alerts
|

Leptin-to-Adiponectin, Adiponectin-to-Leptin Ratios, and Insulin Are Specific and Sensitive Markers Associated with Polycystic Ovary Syndrome: A Case–Control Study from Bahrain

Abstract: In Bahraini women with PCOS, insulin, L/A, and A/L ratios seem to be the best markers to distinguish women with and without PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 36 publications
7
17
0
Order By: Relevance
“…We found that overweight/ obese women with or without PCOS had lower adiponectin and higher leptin levels than lean women. Our study also confirmed the findings in a previous report that the adiponectin/leptin ratio is a marker of PCOS [18]. Furthermore, our results were the first to suggest opposing roles of adiponectin and leptin in overweight/ obese and lean women with PCOS.…”
Section: Discussionsupporting
confidence: 92%
“…We found that overweight/ obese women with or without PCOS had lower adiponectin and higher leptin levels than lean women. Our study also confirmed the findings in a previous report that the adiponectin/leptin ratio is a marker of PCOS [18]. Furthermore, our results were the first to suggest opposing roles of adiponectin and leptin in overweight/ obese and lean women with PCOS.…”
Section: Discussionsupporting
confidence: 92%
“…It was proposed that the adiponectin/leptin ratio is a better inflammatory marker than adiponectin or leptin alone (42), given its high sensitivity and specificity in diagnosing metabolic syndrome, independent of BMI (43). The association of the adiponectin/leptin ratio with PCOS is in agreement with the results of a recent smaller study on Bahraini women with PCOS (34). The main difference between both studies is the magnitude of association; AUC values of 0.937 and 0.861 were reported by the study of Golbahar et al (34), compared with our 0.671 and 0.650 for insulin and adiponectin/leptin ratios, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…Higher ROC AUC values, which measure test sensitivity and specificity, were recorded for adiponectin/ leptin and adiponectin/resistin ratios compared with individual adipokines including adiponectin, hence suggesting that adipokine ratios may constitute a biomarker of PCOS. This was reminiscent of an earlier study that enrolled a smaller number of women with PCOS and controls (50 per group), which reported on the superiority of adiponectin/ leptin and leptin/adiponectin ratios over adiponectin or leptin in predicting PCOS; the notable difference was in the magnitude of the association (34). This difference is likely attributable to the differences in sample size, characteristics of the study participants, and the method used for the adipokine assays.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations